Pandemic inequity in a megacity: a multilevel analysis of individual, community and healthcare vulnerability risks for COVID-19 mortality in Jakarta, Indonesia - Surendra, H; Salama, N; Lestari, KD; Adrian, V; Widyastuti, W; Oktavia, D; Lina, RN; Djaafara, BA; Fadilah, I; Sagara, R; Ekawati, LL; Nurhasim, A; et al. (BMJ Publishing Group, 2022)
Introduction Worldwide, the 33 recognised megacities comprise approximately 7% of the global population, yet account for 20% COVID-19 deaths. The specific inequities and other factors within megacities that affect vulnerability to COVID-19 mortality remain poorly defined. We assessed individual, community-level and healthcare factors associated with COVID-19-related mortality in a megacity of Jakarta, Indonesia, during two epidemic waves spanning 2 March 2020 to 31 August 2021.